Remarks on the types of three accepted names in Limonium (Plumbaginaceae) described from the eastern Iberian Peninsula - Ferrer-Gallego, P. Pablo; Laguna, Emilio; Crespo, Manuel B. (Phytotaxa, 2021)
The typification of three names in the genus Limonium published by Sandro Pignatti from the eastern Iberian Peninsula (L. confusum subsp. densissimum, L. lucentinum, and L. parvibracteatum) is discussed. The personal herbarium of Prof. Sandro Pignatti was originally deposited at TSB (Herbarium of the University of Trieste - Herbarium Universitatis Tergestinae, Friuli-Venezia region, NE Italy). However, all holotypes of the genus Limonium are no longer kept at the herbarium TSB, since S. Pignatti transferred them to the herbarium RO (“La Sapienza” University of Rome, Lazio region, C Italy) in the early 1980s. However, at RO there is only the holotype (or perhaps the lectotype) of L. confusum subsp. densissimum. Threfore, the names L. lucentinum and L. parvibracteatum are lectotypified using Pignatti’s original specimens from GOET and RO, respectively.